Checking Behaviours, Prospective Memory and Executive Functions. Issue 2 (29th May 2015) - Palmer, Lorna Elise; Durkin, Kevin; Rhodes, Sinéad M.
<x content-type="archive" xml:space="preserve">Abstract</x> Explanations implicating memory in the causes and severity of checking symptoms have focused primarily on retrospective memory, and relatively little attention has been paid to prospective memory. Limited research has examined the relationship between prospective memory and executive functions. We assessed whether impairments in prospective memory and executive function predict checking symptoms in a sample of 106 adults. Checking symptoms were assessed using the Padua Inventory Washington State University Revision (PI-WSUR). All participants completed the prospective memory questionnaire (PMQ) and four computerised executive function tasks from the CANTAB, measuring inhibition, planning, attention set-shifting and working memory. Prospective memory and inhibition predicted checking symptom severity. Importantly, there were no correlations between internally cued prospective memory and inhibition or between prospective memory aiding strategies and inhibition. These variables appear to have an independent role in checking. The current findings highlight prospective memory and inhibition as key contributors to the checking symptom profile and provide the first evidence that these cognitive processes may independently contribute to checking symptoms. These findings have implications for a model in which memory performance is thought to be secondary to impairments in executive functions.